Application of thermography for monitoring stomatal conductance of Coffea arabica under different shading systems - Craparo, Alessandro Carmelo William; Steppe, K.; Asten, Piet J.A. van; Läderach, Peter R.D.; Jassogne, Laurence T.P.; Grab, S.W. (Elsevier, 2017)
Stomatal regulation is a key process in the physiology of Coffea arabica (C. arabica). Intrinsically linked to photosynthesis and water relations, it provides insights into the plant's adaptive capacity, survival and growth. The ability to rapidly quantify this parameter for C. arabica under different agroecological systems would be an indispensable tool. Using a Flir E6 MIR Camera, an index that is equivalent to stomatal conductance (Ig) was compared with stomatal conductance measurements (gs) in a mature coffee plantation. In order to account for varying meteorological conditions between days, the methods were also compared under stable meteorological conditions in a laboratory and Ig was also converted to absolute stomatal conductance values (g1). In contrast to typical plant-thermography methods which measure indices once per day over an extended time period, we used high resolution hourly measurements over daily time series with 9 sun and 9 shade replicates. Eight daily time series showed a strong correlation between methods, while the remaining 10 were not significant. Including several other meteorological parameters in the calculation of g1 did not contribute to any stronger correlation between methods. Total pooled data (combined daily series) resulted in a correlation of ρ = 0.66 (P ≤ 2.2e − 16), indicating that our approach is particularly useful for situations where absolute values of stomatal conductance are not required, such as for comparative purposes, screening or trend analysis. We use the findings to advance the protocol for a more accurate methodology which may assist in quantifying advantageous microenvironment designs for coffee, considering the current and future climates of coffee growing regions.